Targeted metabolomics as a tool for the diagnosis of kidney disease in Type II diabetes mellitus. Issue 4 (2nd October 2021) - Abdelsattar, S; Kasemy, ZA; Elsayed, M; Elrahem, TA; Zewain, SK
ABSTRACT: Background : Diabetic kidney disease (DKD) is an increasing health problem and an extra burden to health services. The study of characteristic metabolic alterations of DKD is crucial for a better understanding of pathogenesis to identify new potential biomarkers and drug targets. We hypothesized that metabolic profiling of amino acids, acylcarnitines, and organic acids are useful new biomarkers for the diagnosis of the early stages of DKD Methods: The hypothesis was testing in a case-control study of 232 patients with type 2 diabetes mellitus and 150 healthy controls. Patients were classified according to urinary albumin and estimated glomerular filtration rate (eGFR) into 100 with normoalbuminuria and 132 with microalbuminuria group. Eighteen AcylCNs and 17 amino acids were measured in the blood by tandem mass spectrometry while 17 urinary organic acids were quantitatively measured by gas chromatography – mass spectrometry. Results: Regression analysis found that dodecanoylcarnitines C12 (effect size 2.03 [95%CI 1.73–2.32]), triglylcarnitine C5:1 (2.01 [1.70–2.30]), and isovalerylcarnitine C5 (1.78 [1.48–2.07]) were stronger predictors of albumin/creatinine ratio than HbA1c (1.50 [1.20–1.78]) and hence they could serve as potential biomarkers for the diagnosis of the early stages of DKD. Conclusions: Targeted metabolic profiling offers a new, non-invasive approach for detecting biomarkers for the early diagnosis of DKD suggesting new pathogenetic phases that might be new targets for treatment.